From space to threatening territory: the representation of the land of Chile in Desengaño and reparo de la guerra del reino de Chile (1614), by Alonso González de Nájera - Donoso Rodríguez, Miguel (2019)
Indian Chronicles usually idealize the space they describe as a form of reclamation, to show the benefits of the territory. Also, they can present Nature as wild and untamed so to explain the difficulties of Conquest. A good example of this is Desengaño y reparo de la guerra del reino de Chile (1614), by Alonso González de Nájera, a heterogeneous work that mixes the natural and moral treatise of the Austral territory and its people with the chronicle or narrative of events; treatise of captivity but at the same time means or memorial to win the Arauco war. Space plays a vital role here: on the one hand, the author uses it to flaunt the beauties of the distant territory of Chile; on the other shows how the rough and wild land provides the Indians with insurmountable advantages in war.